Emergency Room Nurses Caring Behaviour Based on Characteristic a Cross-sectional Study - Hafidz Ma'ruf; Harjati Harjati (Universitas Respati Yogyakarta, 2023)
The nurses caring behaviour in the Emergency Room (ER) in Indonesia is still relatively low. Several studies state that factors that influence nurses caring behavior are age, marital status, work experience, and educational level. This study contributed to determining whether the differences in the ER nurse characteristics affected the caring behavior of the ER nurses. This study used a cross-sectional design. A total of 14 ER nurses and 28 ER patients were involved. The instrument uses the Gadar Caring Scale in the behavioral domain. Analysis used independent T-test and ANOVA. The results show that most of the respondents were women (78.6%), aged between 31-40 years (50%), had a D3 degree in nursing (92.9%), married (85.7%), and had worked for 10 to 20 years (50%). There was no difference between the characteristics of gender (p=0.36), age (p=0.53), education (p=0.31), marital status (p=0.94), and length of work in the hospital (p=0.24) in ER nurses caring behavior. The conclusion of this study was that the different characteristics of the ER nurses did not affect the caring behavior of the ER nurses. It was hoped that the nurse’s caring behavior would always be optimal because it’s important in the patient’s recovery.